2016
DOI: 10.1080/13501763.2016.1158203
|View full text |Cite
|
Sign up to set email alerts
|

The scheduling power of the EU Council Presidency

Abstract: KEY WORDSAgenda-setting; Council of the European Union; political attention; Presidency; scheduling power

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Similarly, König and Proksch (2006) treat the Council president as the agenda-setter once the Commission has introduced a proposal and makes the final offer to the Member States. These claims are supported by a substantial number of studies presenting evidence that rotating presidents tend to have significant agenda-setting powers (Häge, 2017;Schalk et al, 2007;Tallberg, 2003Tallberg, , 2010Thomson, 2008;Warntjen, 2008Warntjen, , 2013a and are able to obtain policy outcomes closer to their ideal preferences (Van Gruisen et al, 2017).…”
Section: Literature and Hypothesesmentioning
confidence: 93%
“…Similarly, König and Proksch (2006) treat the Council president as the agenda-setter once the Commission has introduced a proposal and makes the final offer to the Member States. These claims are supported by a substantial number of studies presenting evidence that rotating presidents tend to have significant agenda-setting powers (Häge, 2017;Schalk et al, 2007;Tallberg, 2003Tallberg, , 2010Thomson, 2008;Warntjen, 2008Warntjen, , 2013a and are able to obtain policy outcomes closer to their ideal preferences (Van Gruisen et al, 2017).…”
Section: Literature and Hypothesesmentioning
confidence: 93%
“…Alexandrova and Timmermans, 2013; Alexandrova et al., 2014). While the effect of the rotating Presidency on the overall allocation of political attention in the Council of the EU has been the subject of past research (Häge, 2017), this is the first quantitative study that focuses on the allocation of political attention across sub-topics within a particular policy area. The idea for the creation of the HR and the EEAS was originally developed in the Constitutional Convention in 2002 (European Convention, 2002); and Convention members’ rationales for the establishment of the post and its administrative support body mirror principal–agent arguments.…”
Section: Making the Eu A More Effective Foreign Policy Actormentioning
confidence: 99%
“…However, even though member states might occasionally challenge a decision by the chair, directing the Council’s attention to a particular issue in a sustained manner across all levels of its hierarchy would be difficult if not impossible without the Presidency’s support. In fact, a number of empirical studies have shown that the chair is quite effective in using its formal and informal prerogative to shape the agenda of the Council (Bengtsson et al., 2004; Crum, 2007; Dür and Mateo, 2008; Häge, 2017; Kleine, 2013a, 2013b; Smeets and Vennix, 2014; Tallberg, 2004, 2006; Warntjen, 2013; Westlake and Galloway, 2004). That does not mean that the chair’s agenda-setting activities do not follow established traditions and precedents, or that the chair is irresponsive to emerging policy problems, but that these structural and external drivers do not fully determine the chair’s agenda-setting behaviour.…”
Section: The Delegation Of Agenda-setting Power To Supranational Chairsmentioning
confidence: 99%
“…Häge (2016) studies a different form of agenda-setting powers: he focuses on scheduling rather than proposal making. His findings suggest that the Presidency has considerable impact in determining what issues the Council discusses and how much time it devotes to them.…”
Section: The Council and Its Presidencymentioning
confidence: 99%